O lazer na Base Nacional Comum Curricular (BNCC): uma análise documental - Carlos Alberto Fonseca (2018)
The thematic relation between leisure and education has been the target of some academic studies, which has highlighted these interfaces in both school and non-school areas. Regarding the school context, disciplines such as art, history, geography, portuguese and foreign languages seem to dialogue with leisure activities; however, there is no consensus on the relationship between leisure and education, and especially how it should be developed in this environment. From this perspective, an understanding of the possibilities of working this theme inside the school, not only in physical education, but also in other disciplines, led me to study official documents, specific to the educational area that could contribute to this discussion. Specifically, I turned to the current debate on the Common National Curricular Base (CNCB) that constitutes the object of research of this study. To that end, I established the following objectives: to describe and analyze how the CNCB addresses leisure, in order to: identify in which areas leisure is mentioned; to detect how these areas approach this theme and analyze which focus has the term leisure in the documents, and finally, to compare the different approaches of leisure in the three CNCB versions. The text of the CNCB has been debated since the year of 2015 and three versions of the document have been produced so far; being the last version approved last December (2017). To extend the discussion of the position of leisure within the school context, this study used the combination of bibliographical research and documentary analysis to verify how the texts addressed this theme. The three versions of CNCB were obtained from the electronic database of the Ministry of Education (MEC) and the analysis focused on the following elements: the historical context in which the documents were produced (political, economic and social scenario); the authors: people and professionals involved with the preparation of the document in different occasions; interests: institutional bodies, professionals in education and society; the reliability of an information relative to the base text; and the key-concept of leisure. These elements were discussed with the assistance of the content analysis technique. In conclusion, I have identified that the term leisure appears in all 3 (three) versions of CNCB and, accordingly, the term is cited 11 times in the first version, 27 times in the second one and 15 times in the third one. I have also identified that leisure is cited in specific texts of different areas of knowledge, such as geography, physical education, art, and history; which may indicate the multidisciplinary character of the term within the school context. In addition, the word leisure, in all versions of the document, is preceded by the terms: practices, use, context, scope and situations. Finally, I suggest that leisure establishes relationships with elements related to body culture, sports, politics, technologies, artistic and cultural plurality, identities and interculturalities.